Academic Institutions' Critical Guidelines for Health Care Workers Who Deploy to West Africa for the Ebola Response and Future Crises*. (14th August 2015) - Cranmer, Hilarie; Aschkenasy, Miriam; Wildes, Ryan; Kayden, Stephanie; Bangsberg, David; Niescierenko, Michelle; Kemen, Katie; Hsiao, Kai-Hsun; VanRooyen, Michael; Burkle, Frederick M.; Biddinger, Paul D.
Abstract: The unprecedented Ebola Virus Disease (EVD) outbreak in West Africa, with its first cases documented in March 2014, has claimed the lives of thousands of people, and it has devastated the health care infrastructure and workforce in affected countries. Throughout this outbreak, there has been a critical lack of health care workers (HCW), including physicians, nurses, and other essential non-clinical staff, who have been needed, in most of the affected countries, to support the medical response to EVD, to attend to the health care needs of the population overall, and to be trained effectively in infection protection and control. This lack of sufficient and qualified HCW is due in large part to three factors: 1) limited HCW staff prior to the outbreak, 2) disproportionate illness and death among HCWs caused by EVD directly, and 3) valid concerns about personal safety among international HCWs who are considering responding to the affected areas. These guidelines are meant to inform institutions who deploy professional HCWs. ( Disaster Med Public Health Preparedness . 2015;9:586–590)